2023
DOI: 10.1002/agj2.21270
|View full text |Cite
|
Sign up to set email alerts
|

Forage yield and biological nitrogen fixation of pea–cereal intercrops for hay production

Abstract: Intercropping forage pea (Pisum sativum L.) with barley (Hordeum vulgare L.) or oat (Avena sativa L.) is an alternative way of cropping to improve forage yield and quality for hay production compared to monocropping. A 2-year (2016-2017) field study was conducted at three sites in Saskatchewan, Canada, to evaluate forage production and biological nitrogen fixation (BNF) of pea-cereal intercrops in comparison to pea, barley, and oat monocrops with and without 60 kg N ha −1 fertilization. Barley and oat were dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For instance, the N transfer from soybeans to sorghum ranged from 32 to 58% [24], while Chu et al [25], showed that N transfer from peanut to rice in intercrop was between 6.2 and 12.2%, depending on the N applied as fertilizer. Similarly, Gungaabayar et al [26] reported N transfer in an intercrop of peas with cereals between 17 and 43%.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, the N transfer from soybeans to sorghum ranged from 32 to 58% [24], while Chu et al [25], showed that N transfer from peanut to rice in intercrop was between 6.2 and 12.2%, depending on the N applied as fertilizer. Similarly, Gungaabayar et al [26] reported N transfer in an intercrop of peas with cereals between 17 and 43%.…”
Section: Introductionmentioning
confidence: 89%
“…This crop is a vital source of plant-based protein for both animal feed and human food, offering significant health benefits (Tulbek et al 2016; Clemente and Olias 2017). Additionally, pea plays a crucial role in agricultural sustainability through nitrogen fixation enhancing soil fertility and structure, making it a valuable component of crop rotation or intercropping systems, particularly in conjunction with cereals (Skoufogianni et al 2019; Gungaabayar et al 2023).…”
Section: Introductionmentioning
confidence: 99%